The Effect of Innovational Performance on Determining Firm Value: Evidence from Indonesia - Handriani, Eka (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2020)
This study explores the most significant determinant of capital structure towards the value of manufacturing companies in Indonesia. Multiple regression models were used as statistical tools to investigate the most significant determinants of the firm value of manufacturing companies in Indonesia for a sample of 300 manufacturing firms listed on the Indonesia Stock Exchange. The results showed that profitability, company size, dividend, investment, and innovational performance were positively related to firm value. Debt was negatively related to firm value and dividend was an insignificant firm value determinant. Meanwhile, the influence of innovational performance variables mediating the effect of investment on firm value showed that the role of mediation innovational performance was able to increase the influence of total investment on firm value. Furthermore, empirical findings will help company managers to make decisions about the attempts to increase the firm value.